An Investigation of Producing Activated Carbon from Moringa Oleifera Seeds Husk - Ali, Eman N.; Anis Farhana, Abd Razak (2014)
Activated carbon is an important adsorbent in many industries. The cost of many products is increasing because of the high price of activated carbon. Therefore, to find an alternative is of great importance. The alternatives can be produced from many plant wastes one of which is Moringa oleifera seeds husks. Three samples were used (mechanically removed husks, manually removed husks, and the fine size of manually removed husks). The seeds husks were carbonized with one stage steam pyrolysis, because the process requires less energy compared to two heating stages. The three samples were heated in a cylindrical pyrolysis reactor which is heated by electrical heater to the required temperature of 600, 700, and 800°C, and the samples were kept at each temperature for an hour. The produced activated carbon was characterized by measuring surface area and adsorption capacity by Langmuir adsorption isotherm and Iodine test. The results showed that three samples are having good properties as activated carbon compared to commercial one. As a conclusion, the Moringa oleifera seeds husks can be considered for more research work to be a good alternative for commercial activated carbon.